Implementasi Kurikulum Merdeka Belajar di Pendidikan Anak Usia Dini (PAUD) - Ashfarina, Indah Noer; Soedjarwo, Soedjarwo; Wijayati W, Dewie Tri (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
This research is motivated by the implementation of independent curriculum for driving schools at every level of education including early childhood education. Independent curriculum is a new curriculum, preparing a new curriculum is not easy for every education unit. This is a polemic that is often felt by schools, including early childhood teachers, at every turn of the curriculum. However, the independent curriculum is not yet mandatory to be applied in every early childhood education institution. There are three alternative options in its implementation. To provide an understanding related to the essence and how to prepare an independent curriculum, it is important to do this research. This type of research is qualitative research. The research location is defined as the place where the research is carried out. The research was conducted in kindergarten Al Ibrah Gresik and kindergarten Sunrise proclamation Gresik. The research instruments used were interviews, observation and documentation studies. The results showed that the independent curriculum goes hand in hand with the concept of independent learning proclaimed by the Minister of Education and culture. In preparing the independent curriculum that needs to be considered is the basic framework and structure of the curriculum. The purpose of National Education is related to the profile of Pancasila students, namely (1) Faith, fear of God Almighty and noble character; (2) independent; (3) work together; (4) global Diversity; (5) critical reasoning; (6) creative. National standards of Education as a reference and framework that has been translated in the curriculum structure, learning principles, and assessment and learning outcomes. In the independent curriculum, the curriculum structure contains intraculricular activities to strengthen the profile of Pancasila students. There are learning achievements that must be achieved in accordance with three elements, namely (1) religious and ethical values; (2) identity; (3) the basics of literacy, mathematics, science, technology, engineering, and art.